Extended blocker, deletion, and contraction maps on antichains - Andrey O. Matveev (International Journal of Mathematics and Mathematical Sciences)
Families of maps on the lattice of all antichains of a finite bounded poset that extend the blocker, deletion, and contraction maps on clutters are considered. Influence of the parameters of the maps is investigated. Order-theoretic extensions of some principal relations for the set-theoretic blocker, deletion, and contraction maps on clutters are presented.